Governança em saúde na microrregião geográfica de Francisco Beltrão no olhar dos secretários municipais de saúde - Santos, Gislene Titon Fortes dos (2018)
The theme of health governance became important from the health pact in 2006 and with the requirement of the Unified Health System (SUS) to be organized regionally and hierarchically. Within a system where the demands are great and resources can not always meet this demand there is a need for agreement among the federated entities to ensure efficient and quality care that results in the optimization of available resources and user satisfaction of the system. Thus, health governance requires the municipal secretaries to be able to manage the resources and politics in an ethical, transparent and inclusive manner, in order to meet the doctrinal and organizational principles of SUS. The objective of this research is to know the perception of the municipal secretaries on the theme of health governance. This is a qualitative and descriptive research based on a sample of the municipal health secretaries that belong to the 8ª Regional of Health of Francisco Beltrão composed of 27 municipalities. We interviewed 19 municipal secretaries in the geographic microregion of Francisco Beltrão. Data collection was carried out through a semi - structured interview with 13 questions related to public health governance in the period from July to December 2017. After, the interview content analysis was transcribed and performed from the variables that responded to the objectives proposed in the research. The identified profile of the municipal health secretary is male (57,8%), with an average age of 48 years old, 63,15% don‘t have a higher education and the same percentage have already worked in the SUS. Of the interviewees, 57,85% did not know or did not comment on the type of SUS management in their municipalities, 21,05% reported practicing full management and 15,78% semi - full. All municipalities presented at least one indicator that is part of the practice of good governance, but there is no clear understanding of what health governance is. Participation in different instances, compliance with legislation, compliance with requests among other mechanisms, that are part of the governance is fulfilled due to the SUS requirement. It is concluded that, one of the central questions of this research is, was the understanding of the municipal health secretaries on the subject of health governance. Even present all the important elements for the implementation of health governance has identified that the municipal health secretaries still do not have clarity of the meaning of the concept of governance.